Spooky sleep-out - Suben, Eric.; Ewers, Joe (New York : Random House, 2001)
Elmo, Zoe, Big Bird, and Grover are camping out in the backyard, but strange noises and shadows make them too frightened to sleep.
Keywords: Camping -- Fiction; Puppets -- Fiction